LITERASI DAN NUMERASI SERTA KREATIVITAS DALAM KEBERSIHAN LINGKUNGAN MASYARAKAT DI DESA RUMAH SUMBUL, KECAMATAN SIBOLANGIT, SUMATERA UTARA - Surbakti, Mariana; Simamora, Suhendra; Tamba, Auwy; Situmorang, Hot Ria; Marpaung, Serifina (Merwinspy Publisher, 2024)
Community service is an activity that aims to help the community in several activities without expecting any form of reward. Community service activities are carried out in Rumah Sumbul Village, Sibolangit District, Deli Serdang Regency, North Sumatra. The method of implementing activities is carried out with survey stages, program planning, collaboration with related parties, implementation of activities, evaluation and documentation. The implementation time of community service activities began on February 5, 2024-February 27, 2024. This research shows that programs designed with the aim of improving literacy, numeracy, and environmental awareness can produce significant results. This demonstrates the potential for these programs to become models that can be adopted by other villages to improve quality of life and sustainable development. The research also emphasizes the importance of education and environmental awareness in achieving the goals of sustainable development and community welfare.